Akad Istisna’ dalam Pemesanan Mas Kawin: Tinjauan Fikih dan Hukum Keluarga Islam - Badri Duja (CV. ITTC INDONESIA, 2025)
This study explores the use of istisna’ contracts in ordering dowries (mahar) in Islamic marriage practices. Istisna’ is a type of sale contract where a buyer requests a custom-made item that will be produced after the agreement. In many modern marriages, dowries such as rings or calligraphy are ordered before the wedding but are not ready at the time of the marriage contract. This research aims to analyze whether such a practice is valid under Islamic commercial law (fiqh muamalah) and Islamic family law. Using a normative legal approach, the study examines classical and contemporary Islamic legal texts, including the Kompilasi Hukum Islam (Compilation of Islamic Law) in Indonesia. The findings show that istisna’ contracts are valid as long as the dowry’s form, price, and delivery time are clearly agreed upon. This contract type offers flexibility for modern Muslim couples but should be documented properly to avoid legal disputes. Therefore, it is important to raise awareness about istisna’ in premarital counseling to ensure compliance with Islamic principles.